The Effect of Integrated Subject-Based Instruction on Learning and Academic Achievement Motivation of Professional-Skills of Students with Special Mental Needs - Ali Mihandost; Zabiholah Alahi; Hamidreza Jangizahi; Majid Kahrazehi (مطالعات روانشناسی تربیتی)
This study aimed to investigate the effect of integrated subject-based instruction on learning and academic achievement motivation of professional-skills of students with special mental needs in Chabahar. The research method was quasi-experimental with pre-test-post-test design (with experimental and control groups). The statistical population of this study consisted of all students of professional skills in Chabahar who were studying in exceptional children's schools in Chabahar in the academic year of 1998-99. The statistical sample consisted of 30 people who were selected through purposive sampling and were divided into two groups of control (15 people) and experimental (15 people). Data collection tools included a 20-item academic achievement motivation questionnaire and a teacher made test. Analysis of covariance was used to analyze statistical data. The results showed that at a significant level of 0.28, integrated subject-based instruction could have an effect on students' academic achievement motivation. This has had a significant effect of 0.22 on the effectiveness of integrated subject-based instruction on learning, and in the meanwhile the effect on the learning index has been more due to the better significance. It can be concluded that integrated subject-based instruction has an effect on the rate of learning and academic achievement motivation of students of professional skills with special mental needs. Keywords: integrated subject-based instruction, learning, academic achievement motivation, special mental needs, professional skills